Thermal modification of the troposphere due to convective interaction - Kininmonth, W. R. (William R.), author; Colorado State University, Department of Atmospheric Science, publisher (Colorado State University. Libraries, 1970)
The erosion and subsequent mixing to the environment of the updraft of mesoscale convective clouds is examined and modeled as a mechanism for the thermal modification of the cloud environment. Atmospheric soundings made near the cloud edge of mesoscale convective systems at Anaco, Venezuela during project VIMHEX indicate that these systems are a sink of heat to the prevailing airflow. The convective mixing model is shown to be capable of explaining this heat exchange and thermal modification. To simulate the effect of an intensifying tropical disturbance the model is applied with higher values of updraft equivalent potential temperature. The model demonstrates that the convective clouds are transformed from a net sink to a net source of heat in the troposphere and remain in phase with the observed thermal changes of tropical disturbances.
CER70-71WRK29.
September 1970.
This study was undertaken while the author was on leave from the Commonwealth Bureau of Meteorology, Australia. The research was sponsored by the Office of Naval Research under Contract No. N00014-68-A-0493-0002 with Colorado State University.
Keywords: Tropospheric thermodynamics; Atmospheric thermodynamics; Convection (Meteorology); Troposphere